2020
DOI: 10.1158/2159-8290.cd-20-0036
|View full text |Cite
|
Sign up to set email alerts
|

Disabled Homolog 2 Controls Prometastatic Activity of Tumor-Associated Macrophages

Abstract: Tumor-associated macrophages (TAMs) are regulators of extracellular matrix (ECM) remodeling and metastatic progression, the main cause of cancer-associated death. We found that disabled 2 mitogenresponsive phosphoprotein (DAB2) is highly expressed in tumor-infiltrating TAMs and its genetic ablation significantly impairs lung metastasis formation. DAB2-expressing TAMs, mainly localized along the tumor invasive front, participate in integrin recycling, ECM remodeling and directional migration in a tridimensional… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 48 publications
0
37
0
Order By: Relevance
“…Emerging evidence suggests that tumor development, progression, and metastasis are influenced by dynamic changes in macrophage polarization. The defined subpopulations of macrophages are responsible for tumor-promoting activities [ 22 , 23 , 24 , 25 ]. Hence, targeting TAMs as novel immunotherapeutic strategies to stop tumor progression and metastasis has attracted increasing attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence suggests that tumor development, progression, and metastasis are influenced by dynamic changes in macrophage polarization. The defined subpopulations of macrophages are responsible for tumor-promoting activities [ 22 , 23 , 24 , 25 ]. Hence, targeting TAMs as novel immunotherapeutic strategies to stop tumor progression and metastasis has attracted increasing attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…However, Chao et al suggested that upregulation of DAB2 could promote EMT by inhibiting E-cadherin while stimulating vimentin and phospho-FAK, indicating the significance of DAB2 in EMT ( Chao et al, 2012 ). In human gastric carcinomas, DAB2 + tumor-associated macrophages correlated with a poor clinical outcome ( Marigo et al, 2020 ). SERPINE1, an inhibitor of tissue plasminogen activator and urokinase, is a fibrinolytic inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Disabled homolog 2 (DAB2), as a member of the disable gene family, has been proven to function as a tumor suppressor that plays an crucial role in the occurrence and progression of various tumors ( Albertsen et al, 1996 ), including colorectal cancer ( Kleeff et al, 2002 ) and epithelial ovarian cancer ( Mok et al, 1998 ). Besides, DAB2 is highly expressed in tumor-infiltrating tumor-associated macrophages ( Marigo et al, 2020 ). DAB2 may attenuate the miR-106b promotion effect on HCC cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%